Health and Safety Risk Analysis with JSA Method (Job Safety Analysis) - Imran, Ali; Nursinah, Andi; B, Muslimin; Kadir, Erni; Rino Vanchapo, Antonius; Suabey, Suningsih; Hermawan, Adi (International Journal of Health Sciences, 2023)
Occupational safety and health in hospitals as health services is an important thing to pay attention to. Nurses as one of the medical personnel in the hospital have risks and hazards that are quite vulnerable in every process of their work. Data found from the PPI (Infection Prevention and Control) committee at DR Tadjuddin Chalid General Hospital Makassar as many as 17 cases of needle stick accidents in the last 5 years, there was 1 case of a slip/fall accident when an inpatient co-worker took the patient to the operating room. The purpose of this study is to describe the level of occupational safety and health risks that can occur in nurses at DR Tadjuddin Chalid General Hospital Makassar. The research design used is qualitative in nature with the approach method, namely risk management with interview guide instruments, observation, cameras for documentation and Job Safety Analysis to identify the risks and hazards of nurses' work. Risk assessment uses a semi-quantitative method. The results of this study indicate that the highest risk in the Emergency Room with a score of 300 (Priority 1) is at the anamnase stage and the patient's vital signs, there is a risk of danger of droplet contact contracting the patient's infectious disease and during infusion there is a risk of needle sticks. The results in the ICU show a risk level with a value of 300 (Priority 1) in the administration of injection drugs, infusion with a risk of needle pricks and in personal hygiene activities with a value of 90, there is a risk of contact with the patient's body fluids, and the results in ordinary hospitalization show a high level of risk with a value of 300 (Priority 1) on the examination of the patient's vital signs with a risk of danger of contact with the patient's body fluids, installation of infusion and administration of injection drugs, risk of needle stick hazard. The conclusion from the research results obtained is that there is a need for technical improvements, it is hoped that better supervision in the implementation of SOPs for nursing actions and the active role of K3 Hospitals in identifying deeper stages of nurse work in hospitals.